(untitled) (Scientific journal of the Fergana State University, 2023)
The present paper deals in the study of the boundary problem of the fourth order equation of the parabolic- hyperbolic type   2 Lu 0 x y     in pentagonal domain. The one-valued solvability of the problem is proved by the methods of integral and differential equations.